Literature Review: Factors Causing Hearing Loss Due to Noise in Industrial Workers - Amalia Layina Ulfa; Lilis Sulistyorini (Universitas Airlangga, 2021)
Introduction: Industry is a place where many individuals work. In the industrial field, one can do work by utilizing. However, high-tech applications can cause noise in industrial areas. The discomfort of this sound may indirectly pose a risk of health problems, including hearing loss. Methods: The method used in this study was a literature review study with an in-depth review of the articles through an electronic article data base with the keywords noise, hearing loss, and industrial workers. Then, a screening was carried out based on articles that have been published in a period of five years, and the sorting of articles was conducted according to the inclusion criteria, namely primary data research with cross sectional design, not descriptive research. Results: The journal research phase resulted in up to 101 papers, with 51 papers screened under pre-determined conditions. Then, sorting based on inclusion criteria resulted in 28 items. Finally, as many as 11 relevant articles and the full text were obtained as a result. Based on the review of the article, it is known that hearing loss that occurs among industrial workers is influenced by several problems in the industry such as the absence of noise measurements, the absence of ear health checks for workers, and the unavailability of ear protection equipment. Conclusion: Based on the review of the articles, it is known that hearing loss is caused by high noise levels. Besides, there are other factors that can affect hearing loss in workers such as age, working period, use of ear protection equipment, and a history of ear disease.Keywords: hearing loss, industry, literature review, noise